AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI 1 TANJUNGBALAI - , Oktarini Khamilah Siregar (Jurnal Akuntansi Bisnis dan Publik; Vol 10 No 2 (2019): JURNAL Akuntansi Bisnis dan Publik, 2019)
This study aims to determine the effect of accountability and transparency in the management of budge and expenditure income (APBS) on the performance of teachers in the state junior high school 1 Tanjungbalai. This type of research is associative/quantitative, with the population and sampel used are all teachers in public junior high school 1 Tanjungbalai. The type of data is primary data in the form of questionnaire results. Data analysis techniques using multiple regression analysis. The result of the questionnaire indicate that accountability of the management of APBS has a positive and significant effect on teacher performance, where tcount 3,475 > ttable 2,048 dan significant 0,002 < 0,05, the transparency of the management of APBS has a positive and significant effect on teacher performance tcount 2.682 > ttable 2,048 and significant 0,010 < 0,05, and the result show that simultaneous accountability and transparency in the management of budge and expenditure income (APBS) a positive and significant effect on the performance of teachers where Fcount 8,333 > Ftable 3,33 and significant 0,001 < 0,05.